Outcome of pregnancies complicated by gestational diabetes: a multi-centre study from the North East of England. (16th November 2010) - Bell, R; Hayes, L; Crowder, D; Bilous, M; Lewis-Barned, N; Brandon, H; Pearson, S; Emmerson, C; Adair, S; Bilous, R
Abstract : Background: Treatment of gestational diabetes (GDM) improves outcomes of pregnancy, and national guidance recommends implementation of risk factor screening and treatment of GDM. This has implications for maternity unit workload. This study describes a contemporary cohort of women with GDM in five maternity units in North East England. Methods: Participating units offered universal screening for GDM by blood glucose measurement at booking and 28 weeks. Data were available for 103 women with GDM who delivered April 2008–June 2009. Large for gestational age (LGA) was defined as birthweight ≥90th centile using published centile charts. Results: Mean (SD) booking body mass index (BMI) was 31.4 (7.2) kg/m 2 . 52% of women were obese at booking (BMI ≥30 kg/m 2 ) and 31% had BMI ≥35 kg/m 2 . 24% had no risk factors for GDM. 20% were diagnosed before 24 weeks gestation and 66% of women received insulin or metformin during pregnancy and 25% received an insulin infusion during labour. There were 105 infants, of which one was stillborn and two had a structural congenital anomaly. Mean (SD) birthweight among singletons was 3394 g (597) and 80% were delivered before 39 weeks gestation. 14% weighed at least 4000 g and 31% were LGA. 31% of women had an elective caesarean section (CS), 52% were induced and 17% had spontaneous onset of labour. Overall 48% of women were delivered by CS. There was no association between mode of delivery and BMI. Conclusions: Women with GDM experience high levels of intervention in labour and delivery. CS rates are high regardless of BMI.